Analisis Penurunan Nilai Aset Tetap Terhadap Kinerja Perusahaan - Najwa Haura Lahya; Annisa Dwi Wilatikta; Keysha Tri Hapsari (Journal of Trends Economics and Accounting Research, 2025)
GoTo is the result of a merger between Gojek and Tokopedia which has various assets that support its operations and business growth, one of which is fixed assets. Fixed assets are one of the important components in a company's financial balance sheet that affect the company's performance. However, in its operational activities, in 2024, GoTo experienced a drastic decrease in fixed assets of IDR 10.9 trillion or around 20.13% compared to 2023. Therefore, this study is intended to identify whether the decrease in the value of fixed assets that occurred affected the company's performance at PT. GoTo Gojek Tokopedia Tbk. Where the research method used in this study is a descriptive qualitative method, which relies on data collection techniques through literature reviews from several sources and analyzes the data obtained using secondary data types to obtain research results. This study shows that the decrease in the value of fixed assets actually has a positive impact on the performance of PT. GoTo Gojek Tokopedia Tbk. This is marked by a decrease in depreciation expenses from IDR 2.67 trillion to IDR 744 billion, increasing net income, reducing losses experienced and maintaining stable cash flow.